Depresión y ansiedad en pacientes adultos bajo tratamiento antineoplásico maligno en el Hospital Oncológico de Solca de la ciudad de Loja en el periodo marzo-julio 2014 - Sánchez Gómez, Karla Esther (2015)
Any physical disease involves a psychological reaction, and many are normal and universal; but cancer has become a first order health threat, triggered serious subject in equal or more important than the underlying disease mismatches. The biopsychosocial connotations of cancer are protagonists pain, suffering and death foretold; it does not allow to see beyond what is real , the consequences and psychosocial derivatives diagnosis and treatment, are a source of dissatisfaction for the oncology population. Talking about cancer is to talk about a serious illness; but to what extent it is a disease of the organ, and from where it the soul, mind, compromising the entire patient. The aggressiveness of this disease, it is logical to understand that treatment should be more aggressive. Such surgery is most often used, but combined with other, the Conservatives results and healing approaches have been well regarded by the oncology population. Psychopathological symptoms in the somatic and psychic converge, resulting from the disease and the conventional approach. The psychiatric morbidity has maintained in the form of anxiety and depressive disorders. Besides cancer morbidity it seems to be associated with dominant personality traits -Oncopatic Personality. Although psychiatric comorbidity evident in the oncology population; in our province and country, it raised little research about it, or at least have been poorly socialized. This research aims to determine the incidence and types of depression and anxiety in patients undergoing malignant cancer treatment in hospital SOLCA of Loja, which aims to establish its dominance and the results are of interest to address and partners at the time of treatment. A non-experimental, analytical, quantitative and cross-sectional observational study, considering psychometric instruments and reagents for measuring clinical interview anxiety, depression and personality traits. They were applied to 103 patients who met inclusion criteria. The analysis of the results accuses predominance mild depression and anxiety in patients undergoing chemotherapy; the prevalence of these disorders was in patients with gastrointestinal cancer; with greater dominance in the female gender and personality traits as the predominant anankastic and ciclotímico in this study. Key words: Depression. Anxiety. Personality traits. Cancer